2019
DOI: 10.1007/s00380-019-01435-9
|View full text |Cite
|
Sign up to set email alerts
|

Association between C-reactive protein levels at hospital admission and long-term mortality in patients with acute decompensated heart failure

Abstract: Background:The C-reactive protein (CRP) levels obtained at hospital admission are associated with the prognosis of several cardiovascular diseases, including acute coronary syndrome. Although the admission CRP level is associated with in-hospital mortality in patients with acute decompensated heart failure (ADHF), there are limited data on the association between the admission CRP level and long-term mortality in patients with ADHF.Methods: This study included consecutive ADHF patients admitted to our institut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 57 publications
7
31
0
Order By: Relevance
“…It is an important index for the diagnosis and assessment of severe pulmonary infectious diseases [17]. Matsumoto's study also showed the value of CRP levels in severe pneumonia [18]. This study showed that CRP levels and the diameter of the largest lung lesion increased as the disease progressed.…”
Section: Discussionmentioning
confidence: 77%
“…It is an important index for the diagnosis and assessment of severe pulmonary infectious diseases [17]. Matsumoto's study also showed the value of CRP levels in severe pneumonia [18]. This study showed that CRP levels and the diameter of the largest lung lesion increased as the disease progressed.…”
Section: Discussionmentioning
confidence: 77%
“…Increased levels of several inflammatory biomarkers, including cytokines such as IL-6, IL-2, IL-7, TNF-α, interferon (IFN)-γ, monocyte chemoattractant protein (MCP)-1, macrophage inflammatory protein (MIP)-1α, granulocytecolony stimulating factor (G-CSF), and CRP, procalcitonin (PCT), lactate dehydrogenase (LDH), erythrocyte sedimentation rate (ESR) and ferritin, have been reported in COVID-19 patients. Among inflammatory biomarkers, CRP levels increase significantly at the early stage of the disease, and a positive correlation between increased CRP levels and disease severity has been described [13,20,33,34]. Tan et al [35] showed that CRP has good diagnostic accuracy in early predicting severe COVID-19 at a cut-off value of 20.42 mg/L (area under the curve [AUC] 0.87, 95% Confidence Interval [CI] 0.10-1.00, sensitivity and specificity 83% and 91%).…”
Section: Inflammationmentioning
confidence: 99%
“…So, also C-reactive protein at admission is associated with in-hospital and long-term mortality. 7 But in our study, other than NT pro-BNP levels were not studied.…”
Section: Discussionmentioning
confidence: 77%